1999
DOI: 10.1016/s0022-2275(20)33398-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of different ceramide species from crude cellular extracts by electrospray ionization tandem mass spectrometry (ESI-MS/MS)

Abstract: Quantitative measurement of different ceramide species from crude cellular extracts by electrospray ionization tandem mass spectrometry (ESI-MS/MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(46 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…Each precursor ion was separated in the first quadrupole (Q1), fragmented in the second quadrupole (Q2), and the product ions were scanned in the third quadrupole (Q3). We found that, as reported before [20,22,25,32], one typical fragment for ceramides is the m/z 264. This is generated with the loss of the acyl group and two molecules of water.…”
Section: Optimization Of Tandem Mass Spectrometrysupporting
confidence: 86%
See 1 more Smart Citation
“…Each precursor ion was separated in the first quadrupole (Q1), fragmented in the second quadrupole (Q2), and the product ions were scanned in the third quadrupole (Q3). We found that, as reported before [20,22,25,32], one typical fragment for ceramides is the m/z 264. This is generated with the loss of the acyl group and two molecules of water.…”
Section: Optimization Of Tandem Mass Spectrometrysupporting
confidence: 86%
“…Tandem mass spectrometry can be a useful method to quantify different forms of ceramide simultaneously. In case of multiple reaction monitoring mode, a prior separation step is not essential as the different transitions are specific to the molecules [20][21][22][23]. However, if tandem mass spectrometry is coupled to high-performance liquid chromatography, the selectivity improves and the method is more robust since the components are separated from the impurities.…”
Section: Introductionmentioning
confidence: 99%
“…The following neutral losses were applied: Phosphatidylethanolamine (PE) 141, phosphatidylserine (PS) 185, and phosphatidylinositol (PI) 277 [68]. Sphingosine based ceramides were analyzed using a fragment ion of m/z 264 [69].…”
Section: Lipid Analysismentioning
confidence: 99%
“…A variety of techniques have been previously used for the separation and analysis of ceramides, including thin layer chromatography, gas liquid chromatography (GLC), or HPLC (12)(13)(14)(15)(16) and, more recently, mass spectrometry (MS) (10,17,18). Molecular species of free ceramides, as regards the fatty acid composition, have been identified and quantitated in different cell types such as human platelets (18), erythrocytes (19), leukemia U937 cells (20), or skin fibroblasts (17). However, all the reported methods required either a multistep preparation of the lipid sample (e.g., pre-purification of the ceramide before anthroylation and HPLC) (20), or expensive mass spectrometry equipment (17).…”
mentioning
confidence: 99%
“…Molecular species of free ceramides, as regards the fatty acid composition, have been identified and quantitated in different cell types such as human platelets (18), erythrocytes (19), leukemia U937 cells (20), or skin fibroblasts (17). However, all the reported methods required either a multistep preparation of the lipid sample (e.g., pre-purification of the ceramide before anthroylation and HPLC) (20), or expensive mass spectrometry equipment (17). A comparative and recent review of the current methods emphasized the lack of a simple technique allowing the simultaneous measurement of sphingomyelin and ceramides in biological samples (21).…”
mentioning
confidence: 99%